Some features of implementation of design model of high-pressure centrifugal compressor stage with inlet guide vanes - V. V. Karabanova; A. D. Vanyashov; V. L. Yusha (Омский научный вестник: Серия "Авиационно-ракетное и энергетическое машиностроение")
The analysis of implementation features of the mathematical model of a transonic centrifugal compressor stage with an input guide vanes (IGV) and a semi-open axial-radial impeller has been carried out. The flow study is performed using the Navier-Stokes equations, closed by the Shear Stress Transport (SST) turbulence model. The simulation is performed for the regulation mode at a reduced rotational speed of 28,076 rpm and two IGV angles of rotation in a wide mass flow range. In the course of the study, the parameters of the design model (density of the mesh, inter-mesh connection of the two elements of the flow path) are considered and the effect of the tip between the impeller blades and the body on the gas-dynamic characteristics of the stage is evaluated. According to the results of the study, the most significant parameters that affect the accuracy of the results obtained are established